Green Tea Suppresses Serum TNF-? and TGF-?1 Levels In Mice Model of Systemic Lupus Erythematosus - Herin Mawarti; Jusak Nugraha; Djoko Agus Purwanto; Joewono Soeroso (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: This study aims to investigate the effects of green tea administration on TNF-a, Hsp70, andTGF-b1 levels in the systemic lupus erythematosus (SLE). Material and methods: A total of 32 micewill be divided into four groups (each 8 mice), namely the control group, the SLE group, the SLE groupwho were given green tea extract at a dose of 500 mg/kg body weight, and the SLE group who were givengreen tea extract at a dose of 1000 mg/kg body weight. Analysis of TNF-a, Hsp70, and TGF-b1 levels wascarried out using the enzyme-linked immunosorbent assay technique. Results: TNF-a and TGF-b1 levelswere significantly increased in the SLE group compared to the control group (p < 0.05). This increase canbe significantly reduced through the provision of green tea, even reaching levels comparable to the controlgroup (p > 0.05). Conclusions: It was concluded that green tea containing EGCG can suppress TNF-a andTGF-b1 in the SLE model. Thus, green tea can be an alternative in immunology modulation in SLE.